2018
DOI: 10.1002/cssc.201802284
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructured d‐Ti3C2/TiO2/g‐C3N4 Nanocomposites with Enhanced Visible‐Light Photocatalytic Hydrogen Production Activity

Abstract: The construction of a 2D–2D heterostructured composite is an efficient method to improve the photocatalytic hydrogen generation capability under visible light. In this work, simple heat treatment of a mixture of g‐C3N4 and delaminated Ti3C2 was used to prepare a series of d‐Ti3C2/TiO2/g‐C3N4 nanocomposites. The d‐Ti3C2 not only acted as the support layer and resource to glue the anatase TiO2 particles and g‐C3N4 layers together but also served as the fast electron transfer channel to improve the photogenerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(36 citation statements)
references
References 76 publications
(74 reference statements)
3
32
0
Order By: Relevance
“…19,31 It was depicted that the numbers of both properties increased for 5 Nb/FST, as compared to the parent FST, indicating substitution of Nb ion into FST lattice as a dopant, had given rise in Ti 4+ vacancies and the release of oxygen due to the supplementary charge that was introduced into the lattice. 20,40 This result supported FTIR analysis when the Ti-O-Ti and Si-O-H network led to a decrease in number peaks, suggesting that the substitution of Nb ions on both band networks was responsible for the growth occurrences. 41,42 Fig .…”
Section: Catalyst Characterization Morphological and Structural Analysessupporting
confidence: 64%
See 3 more Smart Citations
“…19,31 It was depicted that the numbers of both properties increased for 5 Nb/FST, as compared to the parent FST, indicating substitution of Nb ion into FST lattice as a dopant, had given rise in Ti 4+ vacancies and the release of oxygen due to the supplementary charge that was introduced into the lattice. 20,40 This result supported FTIR analysis when the Ti-O-Ti and Si-O-H network led to a decrease in number peaks, suggesting that the substitution of Nb ions on both band networks was responsible for the growth occurrences. 41,42 Fig .…”
Section: Catalyst Characterization Morphological and Structural Analysessupporting
confidence: 64%
“…This is most likely due to Nb 5+ having a slightly bigger ionic radius of 0.64 Å as compared to Ti 4+ (0.61 Å). 20,[24][25][26][27] The results are in good agreement with the crystallite size (- Table S1), which revealed that the increase of Nb 2 O 5 loading up to 5 wt% resulted in the crystallite size growing from 29.9 nm to 49.9 nm. Further incorporation of Nb 2 O 5 , up to 10 wt%, led to small shifting with a decreasing crystallite size to 35.0 nm.…”
Section: Photodegradation Activity Of Phenolsupporting
confidence: 62%
See 2 more Smart Citations
“…It is a simple method which can lead to higher purity due to the absence of processing additives and solvents. [21][22][23][24][25][26][27][28] Mechanochemical synthesis can be used to synthesize multicomponent compounds simply by mixing the chemical precursors in the appropriate stoichiometry. Impor-www.advopticalmat.de mixed accordingly to the targeted compound's stoichiometry MA 0.8 Cs 0.2 Pb(Br 0.6 Cl 0.4 ) 3 inside a nitrogen-filled glove box and introduced in a 10 mL zirconia ball-mill jar together with zirconia beads.…”
Section: Doi: 101002/adom201901494mentioning
confidence: 99%